Morphological Regulation Mechanism of Tubular Ferrous Oxalate: Theoretical and Experimental Study. Issue 9 (28th February 2023) - Xu, Peilin; Chen, Xiumin; Wu, Jian; Liu, Li; Yin, Qi; Liu, Bo; Yang, Lianfeng; Zhao, Xiran; Xu, Baoqiang; Jiang, Wenlong; Liu, Dachun; Yang, Bin
Abstract: The formation mechanism and morphology regulation mechanism of tubular ferrous oxalate were investigated by density functional theory. The calculation results showed that the pH value of the reaction solution changed from slightly alkaline to acidic was an important condition for the formation of tubular ferrous oxalate. The size and dispersion of ferrous oxalate can be controlled by introducing Na + and ethylene glycol (EG) into the reaction system. Guided by theoretical calculations, using sodium oxalate as material to guarantee the initial solution to be slightly basic, while also introducing Na + . Regular tubular ferrous oxalate was successfully obtained by using different ratios of EG and H2 O as reaction solution and adjusting pH values at different stages, verified the rationality of the theoretical calculation results. The tubular ferric oxide was obtained by thermal decomposition using tubular ferrous oxalate as the precursor, and the electrochemical performance test results showed that this material is a potential electrode material for supercapacitors. Abstract : The formation mechanism and morphological regulation mechanism of ferrous oxalate tubular were studied by density functional theory, and experiments were carried out to prepare ferrous oxalate tubular on the basis of theoretical calculation.